2002
DOI: 10.1021/jo025957u
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of β-Amino Acid Derivatives Incorporating a Broad Range of Substitution Patterns by Enolate Additions totert-Butanesulfinyl Imines

Abstract: Addition of Ti(Oi-Pr)(3) ester enolates to tert-butanesulfinyl aldimines and ketimines provided beta-substituted, alpha,beta- and beta,beta-disubstituted, alpha,beta,beta- and alpha,alpha,beta-trisubstituted, and alpha,alpha,beta,beta-tetrasubstituted beta-amino acid derivatives in high yields and with high diastereoselectivites. The N-sulfinyl-beta-amino ester products were further employed as versatile intermediates for both standard solution-phase and solid-phase synthetic transformations, including the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(101 citation statements)
references
References 32 publications
8
93
0
Order By: Relevance
“…As shown in Table 5, the reactions of β-amino imines 3, except 4-chlorophenyl-and furyl-β-amino imines (3b and 3h) (Entries 2 and 7), with ethyl acetate/LDA exhibited high diastereoselectivities (99:1 dr) without using any additives such as ClTi(OiPr) 3 . [16] The results of the nucleophilic addition of Grignard reagents to β-amino imines 3 are shown in Table 6. Benzylmagnesium bromide could react smoothly with aryl-β-amino imines 3a, 3d-e, as well as styryl-β-amino imine 3i to afford the chiral 1,3-diamines 9 in very high diastereoselectivities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 5, the reactions of β-amino imines 3, except 4-chlorophenyl-and furyl-β-amino imines (3b and 3h) (Entries 2 and 7), with ethyl acetate/LDA exhibited high diastereoselectivities (99:1 dr) without using any additives such as ClTi(OiPr) 3 . [16] The results of the nucleophilic addition of Grignard reagents to β-amino imines 3 are shown in Table 6. Benzylmagnesium bromide could react smoothly with aryl-β-amino imines 3a, 3d-e, as well as styryl-β-amino imine 3i to afford the chiral 1,3-diamines 9 in very high diastereoselectivities.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, chiral N-sulfinyl imines have been widely used in the nucleophilic addition reaction. [15,16] Recently, Ellman reported the deprotonation of N-sulfinyl ketimines to provide metalloenamines, which were subsequently applied in a series of reactions with electrophiles, such as α-alkylation, [17] Michael addition, [18] and addition to aldehydes, [19] as well as the self-condensation reactions of N-(tert-butylsulfinyl) aldimines. [4] In most cases, high diastereoselectivities and good yields were achieved by using metal salts and other additives after deprotonation.…”
Section: Introductionmentioning
confidence: 99%
“…Typical Mitsunobu conditions (PPh 3 and diethylazodicarboxylate (DEAD) or diisopropylazodicarboxylate (DIAD)) are well suited to achieve pyrrolidine ring closure. This reactivity was first evidenced serendipitously with the unexpected cyclization of 55 to 56 [55] and has later provided synthetic solutions in target oriented-synthesis for cases in which other cyclization conditions were not applicable or failed. [56] Interestingly, this chemistry has been used to develop a very elegant access to stereodefined 2,2,3-trisubstituted pyrrolidines through a highly diastereoselective Mitsunobu cyclization governed by the chiral tert-butanesulfinyl group.…”
Section: Mitsunobu Cyclizations Of Tertbutanesulfinamidesmentioning
confidence: 99%
“…We have found that the addition of titanium enolates to N-sulfinyl imines is extremely general and proceeds in high yields and selectivities for the preparation of β-substituted, α,β-and β,β-disubstituted, α,β,β-and α,α,β-trisubstituted, and even α,α,β,β-tetrasubstituted β-amino acid derivatives (eq. 6) [10,11].…”
Section: © 2003 Iupac Pure and Applied Chemistry 75 39-46mentioning
confidence: 99%